The Role of Biological Sex in Severely Traumatized Patients on Outcomes. Issue 4 (April 2015) - Trentzsch, Heiko; Lefering, Rolf; Nienaber, Ulrike; Kraft, Robert; Faist, Eugen; Piltz, Stefan
<x xml:space="preserve">Abstract</x> Objective: Analyze sex differences in TraumaRegister DGU (TR-DGU). Background: Sex differences are considered to influence trauma outcomes. However, clinical study results are controversial. Methods: Of 29, 353 prospectively recorded cases of TR-DGU, we included primary trauma room admissions with Injury Severity Score of 9 or more into the analysis. Pairs (n = 3887) were formed from 1 male and 1 female according to age, mechanism, injury severity by Abbreviated Injury Scale (for head, thorax, abdomen, extremities), and occurrence of prehospital shock. Biochemical markers, treatment modalities, length of stay, and outcome (multiple organ failure, sepsis, mortality rates) were assessed. Statistical significance was accepted at P < 0.05. Odds ratios (ORs) are given with 95% confidence interval (CI). Results: Females had less multiple organ failure [OR: 1.18 (95% CI, 1.05–1.33); P = 0.007], particularly in age group of 16 to 44 years; sepsis [OR: 1.45 (95% CI, 1.21–1.74); P < 0.001]), particularly at age more than 45 years; and mortality [OR: 1.14 (95% CI, 1.01–1.28); P = 0.037]. Prehospital chest tube insertions (214 vs 158) and surgical procedures before intensive care unit admission were more often performed in males (79.7% vs 76.4%). Females had lower mean hemoglobin levels [10.7 ± 2.6 vs 11.9 ± 2.8 (mg/dL)]. There were no sex differences in fluid resuscitation, shock index, coagulation, and base excess. Conclusions: Males are more susceptible to multiple organ failure, sepsis, and mortality after trauma. Differences were not exclusively related to reproductive age and thus cannot be attributed to sex hormones alone. Females aged 16 to 44 years seem to tolerate shock better. Higher susceptibility to sepsis might be explained by male immune function or increased systemic burden from higher rates of surgical interventions.